The Role of Vitamin D3 in Skin Pigments - Thamer, Rasha; Al-Sadoun, Hamed (International Journal of Psychosocial Rehabilitation, 2020)
The relationship of vitamin D3 deficiency and increased melanin production that leads to appearances of facial pigments such as melasma, unevenness, and hyperpigmented patches. The sample size was 28 individuals; the study was a comparative study. Group A was 9 individuals with real vitamin D3 deficiency < 12 ng/ml according to WHO definition; group B was 13 individuals with normal vitamin D3 levels; 6 individuals didn’t complete the study. The study lasts for 5 months, from May to October 2019. Follow-up visits on a regular baseline, one after 3 weeks, one after another 3 weeks, and the last visit after completion of the 12 weeks. The results of a response to the current study showed that the response rate to vitamin D therapy was very good compared to the rest of the subjects and for all groups. Where the non-response rate was zero, and the poor response rate was from 10% and above, the average response rate was from 50% to 60%, while the good rate was from 60% to 70%, while the highest response rate was from 80% and above, and in figure 1, it explains the difference between before and after treatment. An investigation had been done. It concluded that vitamin D3 has an effect on improving and treating skin pigments.